The development of instrument for real-time monitoring of heavy metal discharge for batik industry - Zukri, Mohammad Nizar Mohamed (2019)
This study presents the development of instrument for monitoring heavy metal discharge in encountering the problem from batik factories. Recently, the rapid growth of batik factories becomes significant issues to sustain environment for the next generation. Due to its properties and composition, heavy metal that by-produced in wastewater is classified as extremely dangerous pollutants to the ecosystem and human health. This Small and Medium Enterprise (SME) industry faces difficulties to regularly monitor the waste discharge since the conventional practice for analyzing heavy metal work in centralized laboratory are conducted offline, low-portability for field work and is an expensive instrument. This study focuses on the development of low-cost device to monitoring heavy metal using an electroanalytical technique equipped with wireless communication module (RFM 95X network chip) to cope with the problem of the conventional practices. This work had employed mathematical algorithm to analyze the existing metal concentration in the solution based on statistical analysis from the data collection using laboratory control sample. In order to ensure the results are robust, other significant parameters such as temperature and acidity (represented in pH) were considered during mathematical formulation development. The control algorithm using PID loop was implemented in the system devices to generate the sufficient voltage input energizing the conductivity sensor. Subsequently, the signal conditioning was applied in the data acquisition system to increase the data quality. The results show that the system promises a good performance with high accuracy compared to other method implemented on previous literature studies. Based on linear regression method, the results indicated from the research work was also proximate to those indicated in the highly-sophisticated equipment such as inductive coupled plasma mass spectrometry (ICP-MS). In conclusion, the research work presented in this thesis promises a success in development of low-cost instrument for online measurement of heavy metal discharge with user friendly feature.